Network basics course booklet (Cisco Networking Academy Program series., 2014)
The Network Basics Course Booklet offers a way for students enrolled in a Cisco Networking Academy Network Basics course to easily read, highlight, and review on the go, wherever the Internet is not available. The text is extracted directly from the online course, with headings that have exact page correlations to the online course. An icon system directs the reader to the online course to take full advantage of the images, labs, Packet Tracer activities, and dynamic activities. The books are intended to be used with the course.